Social Intelligence, Love, Self-Regulation Pada Remaja yang Adiksi Game Online Jenis Agresif dan Non-Agresif - Rizka Apriani; Devy Probowati; Henny Indreswari; Irene Maya Simon (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2020)
Abstract: The internet of things, which was known in the era of the industrial revolution 4.0, can make it easier for teenagers to get information and access the internet everywhere. Excessive use of the internet and always sacrificing important activities by teenagers can be called information technology addiction. Examples of information technology addictions that have a negative impact are aggressive and non-aggressive online game addiction. The negative impact of online game addiction for adolescents is the disruption of social development, social interaction, self-esteem, sympathy, affection for others, and the inability to control themselves. The study aimed to examine the description of social intelligence, love, and self-regulation in adolescents with aggressive and non-aggressive online game addiction. The research population of adolescents from junior high and high school education levels in Malang City. This research uses a quantitative approach with a survey design. The instruments used were an online game addiction questionnaire, a social intelligence questionnaire, a love questionnaire, and a self-regulation questionnaire which was tested for validity and reliability using the Rasch Model. The results showed 1) the majority of adolescents experienced the more aggressive type of online game addiction than non-aggressive online games; 2) the majority of adolescents experiencing aggressive and non-aggressive types of online game addiction have low social intelligence, love, and self-regulation. Abstrak: Internet of things yang dikenal pada era revolusi industri 4.0 dapat mempermudah generasi remaja untuk mendapatkan informasi dan mengakses internet dimana-mana.Penggunaan internet yang berlebihan dan selalu mengorbankan kegiatan penting oleh remaja dapat disebut dengan adiksi teknologi informasi. Contoh adiksi teknologi informasi yang berdampak negatif yaitu adiksi game online jenis agresif dan non agresif. Dampak negatif dari adiksi game online bagi remaja adalah terganggunya pengembangan sosial, interaksi sosial, harga diri, simpati, kasih sayang kepada orang lain, dan tidak mampu mengontrol dirinya. Tujuam penelitian adalah untuk menelaah gambaran social intelligence, love, dan self-regulation pada remaja yang adiksi game online jenis agresif dan non agresif. Populasi penelitian remaja yang dari jenjang pendidikan SMP dan SMA di Kota Malang. Penelitian menggunakan pendekatan kuanititif dengan desain survei. Instrumen yang digunakan adalah kuesioner adiksi game online, kuesioner social intelligence, kuesioner love, dan kuesioner self-regulation yang di uji valid dan realibitas menggunakan Rasch Model. Hasil penelitian menunjukkan 1) sebagian besar remaja lebih banyak mengalami adiksi game online jenis agresif dibandingkan game online jenis non agresif; 2) sebagian besar remaja mengalami adiksi game online jenis agresif dan non agresif memiliki social intellogence, love, dan self-regulation rendah